PENGARUH KUALITAS PELAYANAN, HARGA DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN PADA ZAFI STUDIO DI MANGARAN SITUBONDO - `Aini, Nur; Ediyanto, Ediyanto; Arief, Muhammad Yahya; Syahputra, Hendra (Relawan Jurnal Indonesia, 2022)
This study aims (1) to determine the effect of variable service quality, price and promotion on purchasing decision variables (2) to determine the effect of variable service quality, price and promotion on purchasing decision variables simultaneously on purchasing decision variables (3) to determine the effect of variable service quality, price and promotion on purchasing decision variables dominantly on purchasing decision variables. The result of this research is multiple linear regression equation Y = 1.968E-16 + 0,830X1 + 0,189 X2 + (- 0,162X3) + e. Service quality has a significant positive effect with a value of 15,030, of 1.986, price has a significant positive effect with a value of 3,101, of 1.986, and promotion has a significant positive effect of -2,686, amounting to 1.986. Simultaneously, service quality, price and promotions affect purchasing decisions with a value of 86,9673, 2.71.. The variable that has the most dominant influence in this study is service quality with a value of 15,030.